Acetylcholinesterase Activity Staining in Freshwater Planarians. Issue 2 (17th February 2023) - Rabeler, Christina; Gong, TaiXi; Ireland, Danielle; Cochet‐Escartin, Olivier; Collins, Eva‐Maria S.
Abstract: The serine hydrolase acetylcholinesterase (AChE) is an important neuronal enzyme which catalyzes the hydrolysis of the neurotransmitter acetylcholine and other choline esters. The breakdown of acetylcholine by AChE terminates synaptic transmission and regulates neuromuscular communication. AChE inhibition is a common mode of action of various insecticides, such as carbamates and organophosphorus pesticides. Freshwater planarians, especially the species Dugesia japonica, have been shown to possess AChE activity and to be a suitable alternative model for studying the effects of pesticides in vivo. AChE activity can be quantified in homogenates using the Ellman assay. However, this biochemical assay requires specialized equipment and large numbers of planarians. Here, we present a protocol for visualizing AChE activity in individual planarians. Activity staining can be completed in several hours and can be executed using standard laboratory equipment (a fume hood, nutator, and light microscope with imaging capability). We describe the steps for preparing the reagents, and the staining and imaging of the planarians. Planarians are treated with 10% acetic acid and fixed with 4% paraformaldehyde and then incubated in a staining solution containing the substrate acetylthiocholine. After incubation in the staining solution for 3.5 hr on a nutator at 4°C, or stationary on ice, planarians are washed and mounted for imaging. Using exposure to an organophosphorus pesticide as an example, we show how AChE inhibition leads to a loss of staining. Thus, this simple method can be used to qualitatively evaluate AChE inhibition due to chemical exposure or RNA interference, providing a new tool for mechanistic studies of effects on the cholinergic system. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Preparing the staining solution Basic Protocol 2 : Fixing, staining, and imaging whole‐mount planarian specimens for visualization of acetylcholinesterase activity